(untitled) (SCIÉNDO INGENIUM, 2025)
This article presents a technical proposal to minimize and recover hazardous waste generated in a vehicle maintenance workshop focused on oil changes for buses and trucks. A descriptive methodology based on direct observation of the processes and documentary analysis was applied, identifying inadequate practices in the management of contaminated oils, filters, rags, and containers. Based on the diagnosis, actions such as source segregation, safe storage, and channeling to authorized managers were implemented. As a result, a 38,0% reduction in hazardous waste generation was achieved, highlighting a 30,0% reduction in used oils and a 23,0% reduction in contaminated filters. Likewise, 100,0% of the collected oils and 65,0% of the metal filters were recovered, representing an overall recovery of 62,0% of the total segregated waste. Overall, the proposal significantly contributed to improving environmental control, reducing operational risks, and strengthening regulatory compliance, positioning itself as a viable and sustainable alternative for hazardous waste management in maintenance workshops.